2019
DOI: 10.3390/molecules24162932
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physicochemical, Microbiological Properties and Bioactive Compounds Content of Grassland Honey and other Floral Origin Honeys

Abstract: The aim of this study was to compare the physicochemical, the microbiological, and the antioxidant characteristics of unifloral honey, polyfloral honey, honeydew, and hay meadows honey. Hay meadow is type of semi-natural grassland with a great floral diversity, an important resource for pollinators. Grasslands are the source of the spring nectar honey obtained in May and June. Water content, sugars (fructose, glucose, sucrose, trehalose, melezitose, maltose, erlose, turanose, and raffinose), electrical conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 36 publications
5
20
3
Order By: Relevance
“…Sucrose, turanose, maltose, and isomaltose were detected in minor amounts. Although earlier studies reported the presence of trehalose and melezitose in certain honey samples 16 18 , our study detected neither. The glucose content in honey samples purchased in China (46.3 ± 3.4%) was significantly lower than that in Japan (49.0 ± 3.1%, p < 0.05, Student’s t -test).…”
Section: Resultscontrasting
confidence: 99%
“…Sucrose, turanose, maltose, and isomaltose were detected in minor amounts. Although earlier studies reported the presence of trehalose and melezitose in certain honey samples 16 18 , our study detected neither. The glucose content in honey samples purchased in China (46.3 ± 3.4%) was significantly lower than that in Japan (49.0 ± 3.1%, p < 0.05, Student’s t -test).…”
Section: Resultscontrasting
confidence: 99%
“…The content of phenolic compounds in Polish buckwheat honey [ 12 ] was twice as high as in the present study, while the TPC in rapeseed, linden and acacia honeys was comparable to the values obtained in our study. Low total polyphenol content in rapeseed and acacia honeys was previously noted in Romanian honeys [ 19 ]. In buckwheat honey from China, the total content of phenols was three times as high as in manuka honey, amounting to 1498 mg/kg.…”
Section: Resultsmentioning
confidence: 81%
“…The highest range of water content was found in multifloral honey, from 15.83% to 20.77%. Studies have shown that the moisture content had a large interval of values, from 4.8% to 22.8%, in multifloral Romanian honey [32,[43][44][45]. Moisture content ranged from 14.15% to 18.94% of honey samples from Mexico and Argentina [21,46].…”
Section: Discussionmentioning
confidence: 99%